Regional and national differences in stroke thrombolysis use and disparities in pricing, treatment availability, and coverage - Souza, Ana Claudia de; Sebastian, Ivy Anne; Zaidi, Wan Asyraf Wan; Nasreldein, Ahmed; Bazadona, Danira; Amaya, Pablo; Elkady, Ahmed; Gebrewold, Meron Awraris; Vorasayan, Pongpat; Yeghiazaryan, Nune; Michel, Patrik; Khatri, Pooja; et al. (International journal of stroke, 2022)
BACKGROUND: Major disparities have been reported in recombinant tissue plasminogen activator (rtPA) availability among countries of different socioeconomic status. - AIMS: To characterize variability of rtPA price, its availability, and its association with and impact on each country's health expenditure (HE) resources. - METHODS: We conducted a global survey to obtain information on rtPA price (50 mg vial, 2020 US Dollars) and availability. Country-specific data, including low, lower middle (LMIC), upper middle (UMIC), and high-income country (HIC) classifications, and gross domestic product (GDP) and HE, both nominally and adjusted for purchasing power parity (PPP), were obtained from World Bank Open Data. To assess the impact of rtPA cost, we computed the rtPA price as percentage of per capita GDP and HE and examined its association with the country income classification. - RESULTS: rtPA is approved and available in 109 countries. We received surveys from 59 countries: 27 (46%) HIC, 20 (34%) UMIC, and 12 (20%) LMIC. Although HIC have significantly higher per capita GDP and HE compared to UMIC and LMIC (p < 0.0001), the median price of rtPA is non-significantly higher in LMICs (USD 755, interquartile range, IQR (575-1300)) compared to UMICs (USD 544, IQR (400-815)) and HICs (USD 600, IQR (526-1000)). In LMIC, rtPA cost accounts for 217.4% (IQR, 27.1-340.6%) of PPP-adjusted per capita HE, compared to 17.6% (IQR (11.2-28.7%), p < 0.0001) for HICs. - CONCLUSION: We documented significant variability in rtPA availability and price among countries. Relative costs are higher in lower income countries, exceeding the available HE. Concerted efforts to improve rtPA affordability in low-income settings are necessary.